SPATIAL IDENTIFICATION OF CRITICAL LOGISTICS INFRASTRUCTURE AS NATIONAL VITAL OBJECTS: A NETWORK RESILIENCE APPROACH TO MEGATHRUST CONTINGENCIES - Sudibyo, Reno; Kurniadi, Anwar; Tawakal, Moh. Iqbal (Republic of Indonesia Defense University, 2026)
PASTE/TEXT YOUR ABSTRAX TEXT HEREThe looming threat of a Megathrust earthquake and tsunami along the southern coast of Java compromises not only human safety but also the operational readiness of regional defense and national security. While existing literature predominantly focuses on outbound evacuation flows, there is a critical gap in assessing the resilience of inbound logistics supply chains essential for emergency response operations. This study aims to identify strategic road segments qualifying as National Vital Objects and to delineate isolated territories necessitating Military Operations Other Than War (MOOTW). By employing a spatial network science approach, specifically utilizing Betweenness Centrality algorithms and Network Robustness simulations within the Palabuhanratu road network, this research models the systemic breakdown of access under tsunami inundation scenario, by applying a binary failure threshold of flow depth hmax 0.3m. The quantitative analysis identifies